2017
DOI: 10.1111/jar.12328
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of high intensity therapists delivering cognitive behavioural therapy to people with intellectual disabilities

Abstract: Findings suggest barriers to accessing IAPT largely remain unaddressed where people with ID are concerned. Services may need to reconsider what constitutes appropriate reasonable adjustments to ensure equitable access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 31 publications
2
31
0
1
Order By: Relevance
“…Our findings also echo previous research which suggested that it is common practice to make reasonable adjustments and modifications to existing treatment protocols to meet specific needs, including the needs related to intellectual disability and health (see Barrowcliff & Evans, ; Carrigan & Allez, ; Fernando & Medlicott, ; Marwood, Chinn, Gannon, & Scior, ). It was evident that while clinicians were usually able to make reasonable adjustments to enable adults with mild‐to‐moderate intellectual disability to engage in treatment, this was more difficult for those with more complex and severe intellectual disability and required alternative and more creative ways to ensure delivery of interventions due to deficits in the persons communication.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings also echo previous research which suggested that it is common practice to make reasonable adjustments and modifications to existing treatment protocols to meet specific needs, including the needs related to intellectual disability and health (see Barrowcliff & Evans, ; Carrigan & Allez, ; Fernando & Medlicott, ; Marwood, Chinn, Gannon, & Scior, ). It was evident that while clinicians were usually able to make reasonable adjustments to enable adults with mild‐to‐moderate intellectual disability to engage in treatment, this was more difficult for those with more complex and severe intellectual disability and required alternative and more creative ways to ensure delivery of interventions due to deficits in the persons communication.…”
Section: Discussionsupporting
confidence: 87%
“…Previous research has identified the rigidity of the service as a reason for patient non‐attendance at IAPT with participants reporting a lack of choices regarding appointment time and difficulties fitting appointments into their lives (Marshall et al, ). Similar findings have been observed in people with learning difficulties where a lack of flexibility in appointment scheduling and discharge policies within IAPT services were observed to be too constraining (Marwood et al, ). Cancer patients are likely to have a number of medical appointments, which, in addition to the side effects of some cancer treatments, may make attending weekly IAPT appointments challenging.…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, supervision with someone with experience in delivering therapy to advanced cancer patients. This finding is supported by Marwood et al () who explored the experience of therapists delivering CBT to people with learning disabilities in which therapists expressed a need for specialist supervision when delivering therapy. Additionally, Naylor et al () suggested that IAPT workers working with physically ill patients require on‐going supervision with professionals, such as clinical health psychologists, with experience of working with the same patient group.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations